Integrated comparative analysis of T-staging of laryngeal carcinoma on parallel versus non-parallel vocal cord CT planes with its potential treatment pitfalls - Adeena Khan; Waleed M. S. Fawzy; Syed Shahid Habib; Mamoona Sultan; Manal Bukhari (PLoS ONE, 2025)
Accurate CT staging plays a crucial role in guiding effective management of laryngeal carcinoma, as endoscopic assessment alone may not provide a comprehensive evaluation of tumor spread. Consequences of non-compliance to parallel vocal cord plane for tumors remained unexplored in existing literature. We aimed to compare T-staging parameters of laryngeal carcinoma on CT neck in non-parallel and parallel to vocal cord axial planes and analyse degree of discrepancy between them. We retrospectively studied 34 larynges with squamous cell carcinoma on non-parallel plane① and parallel to vocal cord plane② axial CT scan. Quantitative (anteroposterior AP, transverse Tr, anterior commissure ACom) and qualitative (site, intralaryngeal and extralaryngeal extension) T-staging variables were interpreted in both planes and differences between them were registered. Kappa analysis was employed to get level of disagreement between tumor reporting of each plane. There was minimal to worse agreement between T-staging in these planes (k = −0.059 to 0.353). Difference between means of ACom was significant, but not AP and Tr dimensions. Categorical variables in plane② showed majority of glottic origin (70.5%) and T1a (38.2%) stage, while plane① had subglottic (52.9%) and T2 (41.1%). Overall plane① showed 41.1% altered staging (mostly T1,T2), out of which 71.2% were upstaged. Rest unaffected larynges (28.8%, n = 20) showed either change in origin (41.2%) or ACom involvement (58.8%). Consequently, 73.5% (n = 25) patients in plane ① manifested at least one change, so can jeopardise targeted management. Results established that non-adherence to reporting on parallel CT larynx can result in significant variability in principal qualitative and quantitative T-stage tumor parameters, hence imperiling patients to over or undertreatment.